2023
DOI: 10.1371/journal.pone.0279652
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-electron microscopy of adipose tissue extracellular vesicles in obesity and type 2 diabetes mellitus

Abstract: Extracellular vesicles (EVs) are cell-derived membrane vesicles which play an important role in cell-to-cell communication and physiology. EVs deliver biological information from producing to recipient cells by transport of different cargo such as proteins, mRNAs, microRNAs, non-coding RNAs and lipids. Adipose tissue EVs could regulate metabolic and inflammatory interactions inside adipose tissue depots as well as distal tissues. Thus, adipose tissue EVs are assumed to be implicated in obesity-associated patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 53 publications
(96 reference statements)
1
8
0
Order By: Relevance
“…It is worth noting that the size distribution and concentration of EVs in serum from men with T2DM or normal glucose tolerance were not different [21]. We earlier analyzed the adipose tissue EV structure by means of cryo-electron microscopy and found no size or morphological differences between such EVs from obese patients with and without T2DM [14]. Observed differences such as the increased total proportion of EVs with internal membrane structures were likely due to obesity-associated disturbance of EV biogenesis [14].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…It is worth noting that the size distribution and concentration of EVs in serum from men with T2DM or normal glucose tolerance were not different [21]. We earlier analyzed the adipose tissue EV structure by means of cryo-electron microscopy and found no size or morphological differences between such EVs from obese patients with and without T2DM [14]. Observed differences such as the increased total proportion of EVs with internal membrane structures were likely due to obesity-associated disturbance of EV biogenesis [14].…”
Section: Discussionmentioning
confidence: 97%
“…We earlier analyzed the adipose tissue EV structure by means of cryo-electron microscopy and found no size or morphological differences between such EVs from obese patients with and without T2DM [14]. Observed differences such as the increased total proportion of EVs with internal membrane structures were likely due to obesity-associated disturbance of EV biogenesis [14]. The amount of EVs secreted by obese adipose tissue increases, and their influence on gene expression in target tissues is supposed to be greater, which can result in the development of obesity-related comorbid diseases [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individual EVs secreted by visceral (VAT) and subcutaneous adipose tissue (SAT) were observed by cryo-electron microscopy. It was found that compared with healthy individuals, the EVs secreted by VAT in T2DM patients had a larger proportion of multilayer structures and an intimal structure, indicating the biological changes of EVs …”
Section: Biomedical Applicationsmentioning
confidence: 98%
“…It was found that compared with healthy individuals, the EVs secreted by VAT in T2DM patients had a larger proportion of multilayer structures and an intimal structure, indicating the biological changes of EVs. 217 Pregnancy Complications. It has been found that the concentration of placental EVs (PEVs) released from the placenta is elevated in pregnancy complications such as preeclampsia, gestational diabetes mellitus, etc.…”
Section: Biomedical Applicationsmentioning
confidence: 99%